A proposed vision of the role of the Educational Supervisor specialized in the development of education teachers Sports in Mosul during the Koruna pandemic from their point of view - م.د. ذاكر محفوظ حامد الدليمي أ.د رياض احمد اسماعيل الاشريفي (الرياضة المعاصرة, 2021)
The research aims to: -